Grid Mapping the Northern Plains of Mars: Geomorphological, Radar, and Water‐Equivalent Hydrogen Results From Arcadia Plantia. Issue 2 (21st February 2019) - Ramsdale, Jason D.; Balme, Matthew R.; Gallagher, Colman; Conway, Susan J.; Smith, Isaac B.; Hauber, Ernst; Orgel, Csilla; Séjourné, Antoine; Costard, Francois; Eke, Vince R.; van Gasselt, Stephan A.; Johnsson, Andreas; et al.
Abstract: A project of mapping ice‐related landforms was undertaken to understand the role of subsurface ice in the northern plains. This work is the first continuous regional mapping from CTX ( ConTeXt Camera, 6 m/pixel; Malin et al., 2007 ) imagery in Arcadia Planitia along a strip 300 km across stretching from 30°N to 80°N centered on the 170°W line of longitude. The distribution and morphotypes of these landforms were used to understand the permafrost cryolithology. The mantled and textured signatures occur almost ubiquitously between 35°N and 78°N and have a positive spatial correlation with inferred ice stability based on thermal modeling, neutron spectroscopy, and radar data. The degradational features into the LDM (latitude‐dependent mantle) include pits, scallops, and 100‐m polygons and provide supporting evidence for subsurface ice and volatile loss between 35 and 70°N in Arcadia with the mantle between 70 and 78°N appearing much more intact. Pitted terrain appears to be much more pervasive in Arcadia than in Acidalia and Utopia suggesting that the Arcadia study area had more widespread near‐surface subsurface ice and thus was more susceptible to pitting or that the ice was less well buried by sediments. Correlations with ice stability models suggest that lack of pits north of 65–70°N could indicate a relatively young age (~1 Ma); however, this could also be explained through regional variations in degradation rates. The deposition of the LDM is consistent with an air fall hypothesis; however, there appears to be substantial evidence for fluvial processes in southern Arcadia with older, underlying processes being equally dominant with the LDM and degradation thereof in shaping the landscape. Plain Language Summary: We mapped ice‐related landforms In Arcadia on the northern plains of Mars. This was the first continuous map at this scale. The maps of these ice related landforms were used to understand the role of ice has in shaping the Martian landscape. We found evidence that suggest that ground ice occurs almost everywhere between 35°N and 78°N. We also found landforms associated with loss of ground ice to be widespread suggesting that Arcadia used to have even more ground ice in the recent past. The pattern of landforms we see suggests that the ground ice is sourced from the air, either as snowfall or direct condensation onto or into the near surface. Key Points: We mapped the latitude‐dependent mantle (LDM) almost ubiquitously from 35°N to 78°N; this correlates with predicted ground ice stability Degradational features into the LDM (pits, scallops, and polygons) suggest ground ice and volatile loss between 35 and 70°N in Arcadia The LDM has air fall origin; however, air fall, fluvial, and underlying processes are equally dominant in shaping the northern plains of Mars